2021
DOI: 10.3390/microorganisms9112184
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights for Metabiotics Production by Using Artisanal Probiotic Cultures

Abstract: Wild probiotic consortia of microorganisms (bacteria and yeasts) associated in the artisanal cultures’ microbiota (milk kefir grains, water kefir grains and kombucha) are considered valuable promoters for metabiotics (prebiotics, probiotics, postbiotics and paraprobiotics) production. The beneficial effects of the fermented products obtained with the artisanal cultures on human well-being are described by centuries and the interest for them is continuously increasing. The wild origin and microbial diversity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 144 publications
(151 reference statements)
0
21
0
1
Order By: Relevance
“…and Lactobacillus spp. [ 18 ]. On the other hand, the term probiotics refers to bacteria that exert beneficial functions on the microbiota.…”
Section: Intestinal Microbiota and Dysbiosismentioning
confidence: 99%
See 1 more Smart Citation
“…and Lactobacillus spp. [ 18 ]. On the other hand, the term probiotics refers to bacteria that exert beneficial functions on the microbiota.…”
Section: Intestinal Microbiota and Dysbiosismentioning
confidence: 99%
“…Strains of Bifidobacterium and Lactobacillus can inhibit pathogen colonization, improve barrier function, and modulate the immune response [ 20 , 21 ]. Synbiotics refer to the functional combination of probiotics and prebiotics, which, through their interaction, have a positive effect on the host [ 18 ].…”
Section: Intestinal Microbiota and Dysbiosismentioning
confidence: 99%
“…Many studies have shown that lactic acid bacteria, yeast, and acetic acid bacteria in the kefir microbiota are located in the exopolysaccharide matrix. It is stated that the polymer matrix supports and protects cells (Pihurov et al, 2021). In the examinations made with SEM, it is stated that a complex packaged biofilm surrounds these microorganisms in the outer part of the kefir grain and consists of unstructured material in the inner part (Schwan et al, 2015).…”
Section: Scan Electron Microscopymentioning
confidence: 99%
“…Organic acids, glycoproteins, bacteriocins, exopolysaccharides, polyphosphates, acetate, propionate, and butyrate constitute the major well-defined structural substances that constitute metabiotics [ 2 ]. Various probiotic strains are a source for thousands of metabolites that contribute to genome stability, cell-to-cell communication, and epigenetic regulation, making them attractive candidates for incorporation into the human diet [ 3 ]. In vivo production of these molecules relates to the producer microorganism and/or the prebiotic utilization capacity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%